The Effect of Reach, Amount Spent, and Frequency on The Number of Clicks on Advertisements Posted in Social Media Platorm of Instagram and Facebook - Winarto Poernomo; Erwin Erwin; Yuyun Karystin Meilisa Suade; Cicilia Dewi (STIE AMKOP, 2022)
Abstract This study examines the impact of social media advertising reach, amount spent, frequency and number of clicks, an empirical study: STIE Ciputra Makassar. The research method used is descriptive and quantitative and uses information from the marketing database. Data analysis with SPSS software using classical hypothesis method and multiple linear regression test. On the based results of the particular study, could be taken conclusion that the number of reach of advertising content, the amount of funds spent on advertising during a period, and the number of our advertisements that people see on social networks have a large influence on the number of clicks which contribute to number of people who visit landing pages as a result of published advertisements. Based on the research, 68.1% is influenced by the three variables being used in this study, and the remaining 31.9% under the influence of other variables that are not being used in this particular study. Keywords: Number of Clicks, Social Media Marketing, Digital Marketing, Digital Advertising.